ANALYSIS OF ISLAMIC LAW ON THE PRACTICE OF MULTIPLE CONTRACTS ON PAWNED RICE FIELDS - Nadiatul Husna (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2019)
Pawn is one of the shortcuts for someone to meet their needs. Likewise, the pawn practice that occurs in Gampong Blang Mane Dua Meunasah, the pawned rice fields will generally be cultivated by the murtahin by renting the rice fields, some are divided by two or one third with a profit-sharing system that is classified as a mukhabarah contract. So in this case it is very apparent that there is the implementation of multiple contracts (rahn and mukha>barah). This research contains the formulation of the first problem, how is the practice of multi-contract in pawning rice fields that occurs in Gampong Blang Mane Dua Meunasah District Simpang Mamplam Bireuen Regency. Second, how is the law of multi-contract practice on pawn of paddy fields in Gampong Blang Mane Dua Meunasah District Simpang Mamplam Bireuen Regency according to Islamic law. The type of research used is field research and uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the pawn practice that occurred in Gampong Blang Mane Dua Meunasah, Simpang Mamplam Subdistrict, Bireuen Regency contained multiple contracts, namely rahn and mukha>barah. This happened because the ra>hin pawned his rice field to the murtahin as debt collateral. The ra>hin and murtahin collaborate to manage the rice fields, the ra>hin manages while the murtahin provides capital, the harvest from the pawned rice fields is divided by 1/3 for the murtahin, and 2/3 for the ra>hin. From the explanation above, it can be concluded that the practice of multi-contract on pawned rice fields that occurs in Gampong Blang Mane Dua Meunasah District Simpang Mamplam Bireuen Regency according to the perspective of Islamic law is valid, because the practice of multi-contract does not lead to things that are forbidden, such as usury, gharar, fraud and so on.